Cardiac fibrosis in end-stage human heart failure and the cardiac natriuretic peptide guanylyl cyclase system: Regulation and therapeutic implications - Ichiki, Tomoko; Schirger, John A.; Huntley, Brenda K.; Brozovich, Frank V.; Maleszewski, Joseph J.; Sandberg, Sharon M.; Sangaralingham, S. Jeson; Park, Soon J.; Burnett, John C. (Journal of molecular and cellular cardiology, 2014)
Left ventricular assist device (LVAD) support has been used in the treatment of end-stage heart failure (HF), however use of anti-fibrotic co-therapies may improve prognosis. Natriuretic peptides (NPs) possess anti-fibrotic properties through their receptors, GC-A/GC-B/NPR-C. We sought to evaluate cardiac fibrosis and the endogenous NP system in end-stage HF with and without LVAD therapy and to assess the anti-fibrotic actions of the dual GC-A/-B activator CD-NP in vitro. Collagen (Col) protein content was assessed by Picrosirius Red staining and NPs, NP receptors, and Col I mRNA expression were determined by qPCR in LV tissue from patients in end-stage HF (n=13), after LVAD support (n=5) and in normal subjects (n=6). Col I mRNA and protein levels in cardiac fibroblasts (CFs) pretreated with CD-NP were compared to those of BNP or CNP pretreatment. The LV in end-stage HF was characterized by higher Col I mRNA expression and Col protein deposition compared to normal which was sustained after LVAD support. ANP and BNP mRNA expressions were higher while CNP was lower in end-stage HF LV. GC-A expression did not change while GC-B and NPR-C increased compared to normal LV. The changes in NP system expression were not reversed after LVAD support. In vitro, CD-NP reduced Col I production stimulated by TGF-beta 1 greater than BNP or CNP in CFs. We conclude that the failing LV is characterized by increased fibrosis and reduced CNP gene expression. LVAD support did not reverse Col deposition nor restore CNP production, suggesting a therapeutic opportunity for CD-NP. •LV in end-stage HF and with LVAD support had more fibrosis than normals.•CNP mRNA was deficient in end-stage HF which was not improved after LVAD.•CD-NP had more anti-fibrotic effects than BNP or CNP in vitro.•CD-NP may be potential CNP replacement and anti-fibrotic therapy in HF.